Coordinating Revenue Incentive Policies in the Caribbean - Ding, Ding.; Kalla, Samira; Rosales Torres, Manuel; Sidibe, Abdoul Karim (Washington, D.C. : International Monetary Fund, 2020)
The pervasive use of tax incentives is costly for the Caribbean countries, yet the benefits seem limited. Better policy coordination at the regional level is needed to help overcome the collective action problems and generate more revenue to support the much-needed infrastructure investment. Using the region's Citizenship-by-Investment (CBI) programs as an example, we also show that a price-quantity coordination mechanism can help achieve an efficient outcome with greater CBI incomes for member countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet